2007
DOI: 10.1177/10598405070230010401
|View full text |Cite
|
Sign up to set email alerts
|

An Audit of Medication Administration: A Glimpse Into School Health Offices

Abstract: Many students require prescription and nonprescription medication to be administered during the school day for chronic and acute illnesses. School office staff members are typically delegated this task, yet these individuals are unlicensed assistive personnel without medical training. Five school nurses developed and participated in a medication audit providing a glimpse into the administration and management of medications in school health offices. The audit included 154 medications. Results of the audit show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 15 publications
0
23
0
Order By: Relevance
“…The children in this study did not mention the public health nurse as a resource as did the children in a Swedish study (Rydstrom et al, 1999). Canham et al, (2007) stated that one in four children took sole responsibility for their medication and mentioned the school nurse as a resource as she has knowledge and expertise. Thus, there seems to be a gap between the children's need of care and the HCP support of teachers and children concerning knowledge, care and follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…The children in this study did not mention the public health nurse as a resource as did the children in a Swedish study (Rydstrom et al, 1999). Canham et al, (2007) stated that one in four children took sole responsibility for their medication and mentioned the school nurse as a resource as she has knowledge and expertise. Thus, there seems to be a gap between the children's need of care and the HCP support of teachers and children concerning knowledge, care and follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has shown that medication errors are common in schools when unqualified staff administer medications. [11][12][13][14] For these and other reasons, it was reported in the national health plan, Healthy People 2010, 15 that school nurses are ''ideally positioned'' to promote and provide health education and reduce health risks for students.…”
mentioning
confidence: 99%
“…Previous studies have demonstrated that medication errors are relatively common in schools. [31,32] Medication administration practices may also differ depending on the individual characteristics of teachers, i.e. at the microsystem level.…”
Section: Discussionmentioning
confidence: 99%